2018
DOI: 10.1002/jcb.27607
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic study of glutaric aciduria, type I: Identification of a novel mutation

Abstract: Glutaric acidemia type I (GA-1) is an inborn error of metabolism due to deficiency of glutaryl-CoA dehydrogenase (GCDH), which catalyzes the conversion of glutaryl-CoA to crotonyl-CoA. GA-1 occurs in about 1 in 100 000 infants worldwide. The GCDH gene is on human chromosome 19p13.2, spans about 7 kb and comprises 11 exons and 10 introns. Tandem mass spectrometry (MS/MS) was used for clinical diagnosis in a proband from Iran with GA-1. Sanger sequencing was performed using primers specific for coding exons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Glutaric acidemia type I (GA I; OMIM # 231,670) is an inherited autosomal recessive neurometabolic disease caused by mutations in the gene encoding the mitochondrial enzyme glutaryl‐CoA dehydrogenase (GCDH; EC 1.3.99.7) of the catabolic pathway of the amino acids lysine (Lys), hydroxylysine and tryptophan (Goodman et al, 1977). The GCDH gene is located on human chromosome 19p13.2, spans about 7 kb and comprises 11 exons and 10 introns (Goodman et al, 1977; Shadmehri et al, 2019). GCDH catalyzes the dehydrogenation of glutaryl‐CoA to glutaconyl‐CoA and its decarboxylation to crotonyl‐CoA.…”
Section: Glutaric Acidemia Type I (Ga I)mentioning
confidence: 99%
“…Glutaric acidemia type I (GA I; OMIM # 231,670) is an inherited autosomal recessive neurometabolic disease caused by mutations in the gene encoding the mitochondrial enzyme glutaryl‐CoA dehydrogenase (GCDH; EC 1.3.99.7) of the catabolic pathway of the amino acids lysine (Lys), hydroxylysine and tryptophan (Goodman et al, 1977). The GCDH gene is located on human chromosome 19p13.2, spans about 7 kb and comprises 11 exons and 10 introns (Goodman et al, 1977; Shadmehri et al, 2019). GCDH catalyzes the dehydrogenation of glutaryl‐CoA to glutaconyl‐CoA and its decarboxylation to crotonyl‐CoA.…”
Section: Glutaric Acidemia Type I (Ga I)mentioning
confidence: 99%
“…The GCDH gene is mapped to chromosome 19p13.2, and >200 disease-causing GCDH mutations have been reported in the Human Gene Mutation Database (HGMD), with racial differences in the types of mutations [1][2][3][4]. The gene mutations in this patient were c.383G>A (p.R128Q) and c.873delC (p.N291Kfs*41), which were inherited from her father and mother, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…They suggested, it may be prevalent among Iranian populations. 23 In 2019, Zayed et al studied 41 Egyptian patients with GA1. They identified a total of 25 variants, of which the following six novel variants were identified.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Ahmadi Shadmehri et al investigated clinical and molecular aspects of GA‐1 in one Iranian patient and showed one novel pathogenic mutation in the GCDH gene: c.1147C > A (p. Arg383Ser). They suggested, it may be prevalent among Iranian populations 23 . In 2019, Zayed et al studied 41 Egyptian patients with GA1.…”
Section: Discussionmentioning
confidence: 99%